Numbers of wintering waterbirds on rivers in eastern England - Mason, Chris F; Macdonald, Sheila M (Wildfowl, 2000)
Waterbirds were counted on three occasions during the winter of 1999-2000 on 22 1-km reaches of river in north Essex and south Suffolk, eastern England. Fourteen species were recorded but only five were frequent: Little Grebe (Tachybaptus ruficollis), Mute Swan (Cygnus olor), Mallard (Anas platyrhynchos), Moorhen (Gallinula chloropus), and Coot (Fulica atra). Mallard was the most numerous species. All five species except Little Grebe congregated at places where they were fed by the public. Only Little Grebe showed an increase in numbers over the winter. Of eight habitat variables measured, only river width was consistently related positively, to waterbird numbers. Despite low densities, it is estimated that riverine populations of Little Grebe, Mute Swan, Mallard and Moorhen in the study area are likely to be larger overall than those on the main reservoirs and estuaries in the catchment.